One Method of Cloud Computing Bandwidth Allocation Based on Fairness - Yiquan Kong (Institute of Advanced Engineering and Science, 2013)
In order to solve the bandwidth allocation unfairness problem in the cloud computing network, one method uses fairness congestion control algorithm, access control list (ACL) and traffic policing and traffic shaping in the paper. The method can rationally solve the problem after analyzing the reason of cloud computing bandwidth allocation unfairness. For illustration, one network video conference example was utilized to show the method in solving bandwidth allocation unfairness problem.The experimental results show network bandwidths are fairly allocated, packet loss ratio and latency is obvious improvement. The method deals with non-adaptive UDP and TCP adaptive flow congestion and provides the end-to-end quality of service over the differentiated services networks, and the bandwidth allocation problem based on fairness in the cloud computing network is solved well. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2059